How are energy transition and energy-related R&D investments effective in enabling decarbonization? Evidence from Nordic Countries by novel WLMC model - Kartal, Mustafa Tevfik; Shahbaz, Muhammad; Taskin, Dilvin; Depren, Serpil Kilic; Ayhan, Fatih (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Public interest in climate change-related problems has been developing with the contribution of the recent energy crisis. Accordingly, countries have been increasing their efforts to decarbonize economies. In this context, energy transition and energy-related research and development (R&D) investments can be important strategic tools to be helpful to countries in the decarbonization of economies. Among all, Nordic countries have come to the force because of their well-known position as green economies. Hence, this study examines Nordic countries to investigate the impact of energy transition, renewable energy R&D investments (RRD), energy efficiency R&D investments (EEF) on carbon dioxide (CO2) emissions by performing wavelet local multiple correlation (WLMC) model and using data from 2000/1 to 2021/12. The outcomes reveal that (i) based on bi-variate cases, energy transition and RRD have a mixed impact on CO2 emissions in all countries across all frequencies; EEF has a declining impact on CO2 emissions in Norway (Sweden) at low and medium (very high) frequencies; (ii) according to four-variate cases, all variables have a combined increasing impact on CO2 emissions; (iii) RRD is the most influential dominant factor in all countries excluding Norway, where EEF is the pioneering one. Thus, the reach proves the varying impacts of energy transition, RRD, and EEF investments on CO2 emissions. In line with the outcomes of the novel WLMC model, various policy endeavors, such as focusing on displacement between sub-types of R&D investments, are argued to ensure the decarbonization of the economies.
Keywords: CO(2 )emissions; Energy transition; R&D investments; Nordic countries; WLMC; GLOBAL CO2 EMISSIONS; ECONOMIC-GROWTH; CARBON EMISSIONS; CONSUMPTION; TRADE; NEXUS; TIME; Environmental Sciences & Ecology